Teste do caráter (anti/pró) cíclico da FINEP e outras instituições financeiras - Mascarenhas, Felipe Mazza (2017)
This dissertation compares the grant agreement to innovation projects by Finep to grant agreements by the brazilian bank system, taking the public banks, including the BNDES, apart from the private banks. Through the use of countercyclical economic policy tools in the fight against the 2008 international financial crisis, it was identified, between 2005 and 2014, that the concessions presented significant correlations with the tax burden, the interest rate, the compulsory reserve and indicators of vigor of economic activity (exchange rate and GDP), as already discussed in Alvarenga et al. (2010), Nozaki (2011), Takeda e Dawid (2009), Prates e Freitas (2013) e Micco e Panizza (2006), respectively. We highlight the credit-activity elasticity estimated in this study, which attributes a countercyclical character to public and pro-cyclical for private banks. This result corroborates much of the literature in the area, highlights the importance of separating public and private sector credit in economic studies and underlines the complementarity of the actions of Finep, BNDES and other public banks.